A study on the correlation of motivation and employee job performance in the BPO industry in Metro Manila - Egargo, Maria Lourdes Bernadette B. (Animo Repository, 2017)
This study investigates the relationship between employee motivation and job performance. It employs a survey research method in collecting data from 10 Business Process Outsourcing Companies in Metro Manila. A total of 100 were sampled out. Linear regression statistical tools were used to determine the relationship as well as the effects of motivation. The results reveal a positive relationship between intrinsic motivation and job performance; and an inverse relationship between a motivation and job performance. It has been found that intrinsic rewards highly affect the employees job performance. The study therefore recommends that Management should not focus on motivation solely but to develop a system that caters motivational needs of their employees since intrinsic factors can greatly contribute in increasing employee productivity because they are powerful motivators if used correctly.